Effects of fermented Artemisia annua on the intestinal microbiota and metabolites of Hu lambs with naturally infected with Eimeria spp. - Shuaiqi Liu; Shuaiqi Liu; Shuaiqi Liu; Shiheng Li; Shiheng Li; Shiheng Li; Shunli Lu; Shunli Lu; Shunli Lu; Mingfan Yang; Manyu Liu; Manyu Liu; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundSheep coccidiosis could disturb the balance of intestinal microbiota, causing diarrhea, and even death in lambs. Chemical drugs are the primary method of treating sheep coccidiosis, but their use will bring drug resistance, toxic side effects, drug residues, and other problems. Chinese herbal medicines are investigated as alternative methods for controlling coccidian infections.MethodsIn this study, the effect of fermented Artemisia annua (FA) on oocysts per gram (OPG), average daily gain (ADG), and expression of inflammatory factors were investigated in lambs that were naturally infected with coccidia.ResultsThe results showed that the FA had similar anti-coccidiosis effect to the original drug, while the FA demonstrated a more significant effect on weight gain, and a better ability to reduce the inflammatory response compared to the unfermented drug during the treatment period (P < 0.05). Furthermore, High-throughput sequencing technology was used to study the effects of FA on intestinal microbiota, and fecal metabolites of naturally infected lambs. The species richness of intestinal microbiota of lambs was significantly improved by FA. The abundance of bacteria unclassified_Muribaculaceae, and UCG_005 were increased by fermentation of A. annua. The abundance of bacteria Escherichia_Shigella, unclassified_Clostridia_UCG_014, and Alistipes was reduced. The prevention, and treatment of coccidiosis by fermentation of A. annua may also be related to a series of metabolites affected by intestinal microbiota, including artemisinin, Lysyl-Proline, and TRP-tyrosine.ConclusionFA was found to have superior anti-coccidiosis, anti-inflammatory, and weight gain effects compared to the original Artemisia annua. Intestinal microbes and metabolites such as unclassified_Muribaculaceae, UCG-005, and Artemisinin were identified, suggesting their potential significance. Alistipes was proposed as a biomarker for predicting intestinal coccidia outbreak risk in lambs, pending further validation. The correlation between microbiota, and metabolites may provide new insights into pathogenic changes associated with Eimeria spp.